Strategi Diferensiasi Produk dan Promosi dalam Pengembangan Pentolicious Bites dan Minat Beli Konsumen di Bengkayang (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This study aims to analyze product differentiation and promotion strategies in the development of Pentolicious Bites business and their influence on consumers' purchase intentions in Bengkayang Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The informants in this study consist of six active Pentolicious Bites consumers, selected based on their weekly purchase frequency. Data analysis was conducted qualitatively through data reduction, data presentation, and drawing conclusions. The research results indicate that product differentiation strategies are carried out through flavor innovations by creating new variants such as spicy meatballs, meatball with corned beef, egg, and pineapple. In terms of promotion, business actors currently utilize WhatsApp, but it is recommended to expand to social media platforms such as Instagram, TikTok, and Facebook to reach a wider consumer base. Additionally, packaging and sales location aspects are also important considerations in enhancing consumer experience and convenience, such as using press-packaging and establishing a fixed selling location. The conclusion of this study is that differentiation strategies, which include product innovation, digital promotion, and improving consumer experience, significantly influence the increase in purchasing interest.